The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/0104-9224/si24.22
|View full text |Cite
|
Sign up to set email alerts
|

Resistência à Corrosão de Juntas Dissimilares dos Aços AISI 316L e da Liga Inconel 718

Abstract: Resumo A soldagem dissimilar (Dissimilar Metal Welds – DMWs), união de dois diferentes materiais metálicos, tem muitas aplicações industriais, com destaque para trocadores de calor nas usinas nucleares. Portanto, devem resistir à corrosão e a esforços mecânicos, entre outros requisitos. Neste trabalho foi abordada a susceptibilidade à corrosão da junta de união (feita por soldagem TIG – Tungsten Inert Gas), de forma autógena, de dois materiais distintos: Inconel 718 e o aço AISI 316L. Foram realizadas soldagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Henderson et al [9] reported the use of dissimilar joints of AISI 316L and Inconel 718 in industrial gas turbine engines. Silva et al [10] studied the corrosion resistance of dissimilar joints of Inconel 718 and AISI 316L welded by GTAW process under different heat inputs and concluded that Inconel 718 and the fusion zone (FZ) have good resistance to pitting corrosion, although in the region close to AISI 316L steel may suffer localized corrosion. Gomes et al [11], using the Hole-Drilling technique, analyzed the presence of residual stresses in dissimilar joints of AISI 316L and Inconel 718, concluding that the interface between the base metal and heat-affected zone (HAZ) of each metal presented residual stress around 300 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Henderson et al [9] reported the use of dissimilar joints of AISI 316L and Inconel 718 in industrial gas turbine engines. Silva et al [10] studied the corrosion resistance of dissimilar joints of Inconel 718 and AISI 316L welded by GTAW process under different heat inputs and concluded that Inconel 718 and the fusion zone (FZ) have good resistance to pitting corrosion, although in the region close to AISI 316L steel may suffer localized corrosion. Gomes et al [11], using the Hole-Drilling technique, analyzed the presence of residual stresses in dissimilar joints of AISI 316L and Inconel 718, concluding that the interface between the base metal and heat-affected zone (HAZ) of each metal presented residual stress around 300 MPa.…”
Section: Introductionmentioning
confidence: 99%